Risk of colorectal cancer associated with lifetime excess weight - Li, Xiangwei; Jansen, Lina; Chang-Claude, Jenny; Hoffmeister, Michael; Brenner, Hermann (JAMA oncology, 2022)
Excess weight is associated with increased cancer risk, but the risk may have been underestimated, as previous studies did not consider cumulative lifetime exposure.To assess the association of cumulative lifetime excess weight with risk of colorectal cancer (CRC).In a population-based case-control study conducted since 2003 in Germany, height and self-reported weight documented in 10-year increments starting at age 20 years up to the current age were obtained from 5635 individuals with CRC and 4515 persons serving as controls. Body mass index (BMI), calculated as weight in kilograms divided by height in meters squared, was calculated for each year of age from age 20 years to the current age by linear interpolation. Excess BMI (eBMI) at each year of age was determined as BMI − 25 and summed across ages to obtain the weighted number of years lived with overweight or obesity (WYOs), determined as year × eBMI. The eBMI was set to 0 in case of a BMI below 25. Associations with CRC risk were estimated for BMI at various ages and for WYOs by multiple logistic regression. Data analyses were performed from June 4, 2021, to December 17, 2021.Relative risk of CRC according to lifetime exposure to excess weight compared with relative risks according to BMI at various ages.The mean (SD) age of the patients with CRC (n = 5635) was 68.4 (10.9) years; 3366 were men (59.7%); mean (SD) age of the control participants (n = 4515) was 68.5 (10.6) years; 2759 were men (61.1%). An association was observed between WYOs and CRC risk, with adjusted odds ratios (ORs) increasing from 1.25 (95% CI, 1.09-1.44) to 2.54 (95% CI, 2.24-2.89) from the first to the fourth quartile of WYOs compared with participants who remained within the normal weight range. Each SD increment in WYOs was associated with an increase of CRC risk by 55% (adjusted OR, 1.55; 95% CI, 1.46-1.64). This OR was higher than the OR per SD increase of eBMI at any single point of time, which ranged from 1.04 (95% CI, 0.93-1.16) to 1.27 (95% CI 1.16-1.39).The results of this case-control study suggest a greater role of cumulative lifetime excess weight for CRC risk than estimated by traditional analyses based on BMI measures taken at a single point.
Gesehen am 19.08.2022